5-type HPV mRNA versus 14-type HPV DNA test: test performance, over-diagnosis and overtreatment in triage of women with minor cervical lesions. Issue 1 (December 2016) - Westre, Bjørn; Giske, Anita; Guttormsen, Hilde; Sørbye, Sveinung; Skjeldestad, Finn
Abstract Background Repeat cytology and HPV testing is used in triage of women with minor cytological lesions. The objective of this study was to evaluate 14-type HPV DNA and 5-type HPV mRNA testing in delayed triage of women with ASC-US/LSIL. Methods We compared a DNA test (Roche Cobas 4800) and an 5-type mRNA test (PreTect HPV-Proofer). In total 564 women were included in the study. Results The sensitivity among solved cases for CIN3+ were 100 % (15/15) for both tests. The sensitivity for CIN2+ of the HPV DNA test was 100 % (38/38) relative to 79 % (30/38) for the 5-type HPV mRNA test. The corresponding estimates of specificity for CIN2+ among solved cases were 84 % (393/466; 95 % CI: 81–88) and 91 % (451/498; 95 % CI: 88–93). The positive predictive values for CIN3+ were 13.5 % (15/111) for DNA+ and 19.5 % (15/77) for 5-type mRNA+. Significantly more women screened with 5-type mRNA than DNA returned to screening (81 % vs 71 %, p < 0.01). Subsequently, significantly fewer women were referred for colposcopy/biopsies/treatment (19 % (105/564) vs 29 % (165/564), p < 0.01). Conclusions 5-type HPV mRNA is more specific than 14-type HPV DNA in delayed triage of women with ASC-US/LSIL. The referral rate for colposcopy was 57 % higher for DNA+ relative to mRNA+ cases (165 vs 105), with the same detection rate of CIN3+, but the 5-type mRNA test had lower sensitivity for CIN2+. It is important to consider the trade-off between sensitivity and specificity of the diagnostic test when designing screening algorithms.